2020
DOI: 10.1128/aem.01561-19
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Classical Strain Improvement of Penicillium rubens on Amino Acid Metabolism during β-Lactam Production

Abstract: To produce high levels of β-lactams, the filamentous fungus Penicillium rubens (previously named Penicillium chrysogenum) has been subjected to an extensive classical strain improvement (CSI) program during the last few decades. This has led to the accumulation of many mutations that were spread over the genome. Detailed analysis reveals that several mutations targeted genes that encode enzymes involved in amino acid metabolism, in particular biosynthesis of l-cysteine, one of the amino acids used for β-lactam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…Therefore, possible reasons for the lack of ACV accumulation are insufficient amino acid or energy supply for the conversion. It has been reported that amino acid synthesis, especially cysteine biosynthesis, can limit the pathway flux [51]; however, our measurements indicated steady cysteine and valine concentrations. In contrast to the 0.009 mmol L −1 DO step experiment, the intracellular AAA concentration decreased only slightly during oscillation experiment I.…”
Section: Oscillation Experimentscontrasting
confidence: 80%
“…Therefore, possible reasons for the lack of ACV accumulation are insufficient amino acid or energy supply for the conversion. It has been reported that amino acid synthesis, especially cysteine biosynthesis, can limit the pathway flux [51]; however, our measurements indicated steady cysteine and valine concentrations. In contrast to the 0.009 mmol L −1 DO step experiment, the intracellular AAA concentration decreased only slightly during oscillation experiment I.…”
Section: Oscillation Experimentscontrasting
confidence: 80%
“…Three AAs serve as building blocks, namely α-aminoadipate, L-cysteine and L-valine. A previous analysis demonstrated that the gene Pc20g04020 is considered to be unique for coding the threonine synthase in P. rubens [35]. It plays a key role in catalyzing the conversion of O-phospho-L-homoserine into L-threonine and phosphate.…”
Section: Discussionmentioning
confidence: 99%
“…Pc13g07730 is annotated as L-threonine deaminase, which removes an amino group from L-threonine, resulting in the production of 2-oxobutanoate and pyruvate. The corresponding enzyme that catalyzes the conversion of glycine and succinal-CoA into 5-aminolevulinate, CoA and CO 2 is 5-aminolevulinate synthase (Pc22g13500), also named as the pyridoxal 5'-phosphate-dependent (PLP) enzyme [35]. These findings suggested that the influence of applied EOs may play an important role in modulating these signaling pathways and, thus, may regulate processes involved in cysteine production, which is very important for beta lactam production [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many T. reesei strains that are used in industry underwent point mutations leading to catabolite de-repression, resulting in increased extracellular enzyme and protein levels compared to their parent strain [ 24 ]. Point mutations also resulted in improved cysteine biosynthesis in P. rubens by the inactivation of enzymatic conversions that compete with the cysteine biosynthetic pathway, which plays a key role in penicillin production [ 248 ]. By site-directed mutagenesis, the thermostability of an A. niger xylanase has been improved, showing up to 80% of its maximal activity after incubation for 2 h at 50 °C in the presence of xylan, compared to only 15% activity for the wild-type enzyme [ 249 ].…”
Section: Recombinant Dna Strategiesmentioning
confidence: 99%